I am Streaming in a Room - Chafe, Chris (Frontiers in Digital Humanities, 2018)
Internet Acoustics is the study of sound traveling through the Internet, treating it as an acoustical medium just like air or water. Real-time streaming of sound, something commonplace nowadays, can be exploited for its own "physics" of propagation. In a digitally-connected telecommunication world, rooms of the kind which will be described enclose remotely collaborating musicians in their own reverberated sound. The ambiance which results is the product of an acoustical loop which creates room-like resonances. They are created between Internet endpoints which recirculate sound echoes on the paths between them.These are synthesized acoustical spaces engineered to resemble actual rooms and distinct from other kinds of online rooms where "room" is used metaphorically for gatherings of users participating in teleconference or chat applications. The present article describes room-like internet reverberation for local area and wide area networking, respectively named LAIR and WAIR. Aspects of the medium, algorithms used and the resulting musical experiences are detailed.